Analisis Produksi Salak di Desa Wonokerto, Kecamatan Turi, Kabupaten Sleman, Provinsi Daerah Istimewa Yogyakarta - Suripto Suripto; Rifka Nur Syabrina Putri (Jurnal Ekonomi Pembangunan, 2020)
This study aims to analyze how big the influence of labor, manure, land area, price, experience to the amount of salak production in Wonokerto Village Turi District Sleman District. Determination of respondents using a simple random sampling method (Simple Random Sampling). Analyzer used is an analysis of the Cobb-Douglas production function. The result of the investigation shows the value of the coefficient of determination (R2) of 0.5342 can be interpreted variable production amount 53.42% in by independent variables studied influenced research, while the rest controlled by other factors. Result of F test of labor variable (X1), manure (X2), land area (X3), price (X4), and experience (X5) simultaneously have a positive and significant effect on the amount of salak production in Wonokerto Village. Furthermore, variable of labor, manure, land area has a real impact on production amount in Wonokerto Village. In contrast, price and experience variables have no significant effect on the amount of salak production.